Mutu Gizi Aneka Kudapan Cokibus - Thresia Dewi Kartini B; Nadimin Nadimin (Politeknik Kesehatan Kemenkes Mamuju, 2021)
Snacks are small meals usually served with drinks, both for daily use and for special occasions. Cokibus snack is a snack that is made to complement the intake of nutrients, especially for children who experience stunting. Makassar City has more malnourished children than other cities/districts, namely 22.1% underweight, 25.2% stunting, and 9.4% wasting. This study aims to determine changes in nutritional quality, namely the levels of macronutrients, iron, and calcium in various Cokibus snacks. This type of research is laboratory research. The sample consisted of 4 kinds of snacks, 1 type of Cokibus consisting of standard, and one substitution treatment of 10% snakehead fish meal. Each sample was repeated twice, so there were 16 samples in total. The research was conducted at the Food Technology Laboratory, Department of Nutrition, Poltekkes, Ministry of Health, Makassar, and the sample was examined at the Quality Control Laboratory of SMTI Makassar. The results showed that per 100 grams of various Cokibuses, the average carbohydrate content decreased -0.1%, protein content increased between 0.21% to 0.72%, fat increased 0.02% to 0.12%, iron increased between 0.43% to 0.63%. Calcium also increased between 0.29% to 0.85%. The snack with the highest increase in nutritional content was Charrot muffins, and the lowest increase in nutritional value was Chobus cupcakes.